A kinematic analysis of the handspring double salto forward tucked on a new style of vaulting table - Ferkolj, M. (Science of Gymnastics Journal, 2010)
At the 2001 world championships in Ghent, the FIG (The International Federation of Gymnastics) replaced the traditional horse with a new vaulting table. The new style table is wider and has a more elastic surface. This has resulted in an increase in the number of male gymnasts performing the forward handspring double salto tucked.. This study aimed to determine important kinematic variables during specific phases of the vault (trajectories, time, velocity, angular velocity, angles) that influence the quality of the handspring double salto forward tucked (Roche). The sample consisted of gymnasts that performed the handspring double salto forward tucked at the 2002 World Championship in Debrecen (N=9). Statistical analyses were carried out using SPSS 15.0, 98 kinematic variables were identified, we reported the most important variables identified during the handspring double salto forward tucked movement.. The handspring forward double salto tucked is becoming a basic element on which new derivations of vaulting movements are based (i.e. piked position, or with turns); it is therefore essential to understand its parameters. The results from this study provide useful information for competitors, coaches, and judges.